Sex Differences in Quadriceps Strength in OA - Berger, M. J.; McKenzie, C. A.; Chess, D. G.; Goela, A.; Doherty, T. J. (International Journal of Sports Medicine, 2012)
The purposes of this study were to determine 1) whether sex differences in quadriceps torque and isotonic power persist when controlling for muscle volume (i. e., torque/muscle volume and power/muscle volume) in participants with knee osteoarthritis (OA) and 2) the factors responsible for potential sex differences. Isometric torque, isotonic power (the product of torque and velocity, measured at 10, 20, 30, 40 and 50% maximal voluntary contraction; MVC) and maximal unloaded velocity were assessed in men (n=16, mean age=62.1±7.2) and women (n=17, mean age=60.4±4.3) with knee OA. Torque and power were normalized to muscle volume. The interpolated twitch technique was used to measure voluntary activation (VA) and evoked twitch and torque-frequency characteristics were measured to obtain information about muscle fibre distribution. Torque and power at all loads were significantly lower in women (p<0.05). Sex differences in power were reduced by 50% when controlling for muscle volume but were still significant at 10–40% MVC (p<0.05). No differences in VA, torque-frequency properties or time-to-peak tension of the evoked twitch were observed (p>0.05). These results suggest that only minor sex differences in torque and power persist when controlling for muscle volume. As VA and contractile property differences were not observed, other factors seem to be responsible.
Keywords: isometric torque; isotonic power; magnetic resonance imaging; interpolated twitch technique; contractile properties